2019
DOI: 10.1111/1750-3841.14611
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Functional Complex Extracts from Lycium barbarum and Grape Seed Enhances Immunity Synergistically In Vitro and In Vivo

Abstract: A mixture of multiple ingredients is often more effective than the individual ingredients. The functions of Lycium barbarum polysaccharide (LBP) glycoconjugate and grape seed procyanidins (GSP) are widely known. Here, we investigated the synergistic immune‐enhancing activity of LBP and GSP. Atomic force microscopy results suggested that the mixture of LBP and GSP exhibited circular structure unlike LBP alone, and the addition of polyphenols may change the spatial conformation of the sugar chain. The changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…However, it seems that polysaccharides ( Lycium barbarum polysaccharides, LBPs), of which the fruit is particularly rich, are the primary bioactive components to determine the beneficial pharmacological effects of the berry [ 11 , 12 , 13 , 14 , 15 ]. Previous studies have shown that Goji berries have antioxidant, anti-aging [ 12 ], antitumoral [ 16 ], anti-inflammatory [ 17 , 18 ], immunomodulatory [ 19 ], gastrointestinal-protective [ 20 ], cardioprotective [ 13 ], retinoprotective [ 14 ], and neuroprotective properties [ 21 ] as well as beneficial effects on several aspects of the reproductive sphere [ 22 , 23 ]. Last but not least, an increasing number of studies are showing the influence of Goji berries on blood glucose level homeostasis, suggesting antidiabetic [ 15 , 24 , 25 , 26 , 27 ] and hypolipidemic effects [ 26 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems that polysaccharides ( Lycium barbarum polysaccharides, LBPs), of which the fruit is particularly rich, are the primary bioactive components to determine the beneficial pharmacological effects of the berry [ 11 , 12 , 13 , 14 , 15 ]. Previous studies have shown that Goji berries have antioxidant, anti-aging [ 12 ], antitumoral [ 16 ], anti-inflammatory [ 17 , 18 ], immunomodulatory [ 19 ], gastrointestinal-protective [ 20 ], cardioprotective [ 13 ], retinoprotective [ 14 ], and neuroprotective properties [ 21 ] as well as beneficial effects on several aspects of the reproductive sphere [ 22 , 23 ]. Last but not least, an increasing number of studies are showing the influence of Goji berries on blood glucose level homeostasis, suggesting antidiabetic [ 15 , 24 , 25 , 26 , 27 ] and hypolipidemic effects [ 26 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are a lot of evidences showing that the berry has numerous potential beneficial effects for the general well-being of the individual and for the prevention and treatment of numerous pathologies [1][2][3][4]. Beside several biological active compounds such as carotenoids, vitamins (riboflavin, thiamin and ascorbic acid) and flavonoids, goji berry is primarily rich in polysaccharides [1] which are responsible for the main beneficial pharmacological effects of the fruit both in vitro [5][6][7][8] and in vivo in various laboratory animal species [9,10] and in clinical trials in humans [11,12]. The effects of the goji berries are mainly studied in laboratory animals such as mice and rats [9,10,13] and only a few trials were conducted using the rabbit [14][15][16] although it is considered a useful experimental animal model [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Monosaccharide composition of the Aap was measured by gas chromatograph (GC) according to previous report (You, Chang, Zhao, Zhuang, & Zhuang, 2019), using GC‐2014 system (Shimadzu Co., Ltd., Kyoto, Japan) equipped with a flame ionization detector and a Rtx‐5 silica capillary column (30 m × 0.25 mm ID × 0.25 µm). Using rhamnose, arabinose, xylose, fucose, mannose, glucose, galactose as the monosaccharide standards.…”
Section: Methodsmentioning
confidence: 99%